2013
DOI: 10.1038/emi.2013.38
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in panD encoding aspartate decarboxylase are associated with pyrazinamide resistance in Mycobacterium tuberculosis

Abstract: Pyrazinamide (PZA) is a frontline anti-tuberculosis drug that plays a crucial role in the treatment of both drug susceptible and multidrug-resistant tuberculosis (MDR-TB). Resistance to PZA is most commonly associated with mutations in the pncA gene encoding nicotinamidase/pyrazinamidase which converts the prodrug PZA to the active form pyrazinoic acid (POA). RpsA (ribosomal protein S1) involved in trans-translation was recently shown to be a target of PZA and mutations in RpsA are found in some PZA-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
162
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(169 citation statements)
references
References 22 publications
3
162
2
2
Order By: Relevance
“…Nevertheless, it is of interest to note that the minor proportion of the mutants was able to confer a phenotype of reduced susceptibility (Table 1). This seems unusual, as it is not seen for other drug-resistant mutants conferring resistance to other TB drugs such as pyrazinamide (PZA) (13). This may be due to the nature of LZD in producing a mixed population during mutant selection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is of interest to note that the minor proportion of the mutants was able to confer a phenotype of reduced susceptibility (Table 1). This seems unusual, as it is not seen for other drug-resistant mutants conferring resistance to other TB drugs such as pyrazinamide (PZA) (13). This may be due to the nature of LZD in producing a mixed population during mutant selection.…”
mentioning
confidence: 99%
“…PCR products were purified and were used for Sanger DNA sequencing. Genomic DNA from the 7 mutants with higher LZD MIC values that did not show mutations in rrl or rplC by Sanger sequencing was subjected to whole-genome sequencing using Illumina MiSeq as described previously (13).…”
mentioning
confidence: 99%
“…The most recent model to be proposed suggested that PZA inhibits the M. tuberculosis aspartate decarboxylase PanD and thereby inhibits synthesis of the essential metabolic cofactors pantothenate and coenzyme A (CoA) (Fig. 1) (25). This model was based on the identification of panD missense mutations in spontaneous PZA-resistant M. tuberculosis laboratory isolates that did not have loss-of-function mutations in pncA.…”
mentioning
confidence: 99%
“…Mutations in potential drug targets PanD, RpsA, and ClpC1, involved in energy metabolism and protein degradation, respectively (14,17,18,28) are less common. However, there are still some clinical strains, such as strain 9739 (20), that do not have any of the known resistance gene mutations in pncA, rpsA, panD, and clpC1 (unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in pncA leading to the loss of PZase activity are the major mechanism of PZA resistance (4,10,11). PZA is known to interfere with multiple functions in Mycobacterium tuberculosis, including cytoplasmic acidification (12), disruption of membrane energy and transport function (12,13), inhibition of the protein degradation pathway via RpsA involved in trans-translation (14) and also ClpC1 protease (15,16), and energy production via PanD (17)(18)(19). Although resistance to PZA is mostly caused by pncA mutations and less commonly by rpsA, panD, and clpC1, clinical strains without these mutations such as 9739 (20) are known to exist.…”
mentioning
confidence: 99%